Windproof and heat-retaining fabric, its manufacturing method, and applications

JP7933349B1Active Publication Date: 2026-10-13GUANGZHOU YICHEN NEW MATERIAL CO LTD
View PDF 29 Cites 0 Cited by

Patent Information

Application Number
JP2026091317
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2025-12-01
Filing Date
2026-05-29
Publication Date
2026-10-13
Estimated Expiration
2046-05-29

Smart Images

  • Figure 0007933349000001
    Figure 0007933349000001
Patent Text Reader

Abstract

This application discloses a windproof and heat-retaining fabric, a method for manufacturing the same, and its applications, relating to the technical field of textile materials. [Solution] The windproof and heat-insulating fabric of the present invention comprises an inner lining layer, a middle nanofiber layer, and an outer windproof fabric, which are laminated in order from the inside to the outside. The inner lining layer is manufactured by blending polyester, nylon, and spandex as raw materials. The middle nanofiber layer contains nanofibers, aerogel powder, and a functional filler, the functional filler containing graphene, rare earth compounds, and functional additives. The outer windproof fabric is knitted with composite yarn, which includes a core yarn and a sheath yarn covering the outside of the core yarn. The manufacturing method of the present invention, through layered manufacturing and composite molding, precise material mixing ratios, and process control, imparts excellent heat retention, windproofness, breathability, antistatic properties, and durability to the manufactured windproof and heat-insulating fabric, making it widely applicable to outdoor sportswear, winter clothing, and functional protective clothing.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This application relates to the technical field of textile materials, and more particularly to windproof and heat-retaining fabrics, their manufacturing methods, and applications. [Background technology]

[0002] Currently, the field of textile technology is developing rapidly, and windproof and heat-retaining fabrics are becoming an important functional fabric, widely applied in outdoor sportswear, winter clothing, and functional protective clothing. The development of such fabrics plays an important role in improving people's wearing experience in cold and windy environments and ensuring the safety and comfort of related workers. As people's living standards improve and their enthusiasm for outdoor activities grows, the market demand is constantly increasing, and the requirements for the performance of windproof and heat-retaining fabrics are also becoming increasingly high.

[0003] In conventional windproof and heat-retaining fabric technology, most products employ heavy materials or multi-layer structures to achieve heat retention. Heavy materials primarily rely on their own material properties to block heat dissipation, while multi-layer structures achieve heat retention through the superposition of different functional layers. However, these methods can result in reduced breathability, bulkiness, and a significant impact on freedom of movement and comfort. Some novel fabrics improve performance by adding special fibers or coatings, such as using a polyester microporous membrane to enhance wind resistance. However, these solutions still fall short in terms of maintaining sustained heat retention, and their manufacturing processes are complex, consume a lot of power, are costly, and have a certain environmental impact. [Overview of the project] [Problems that the invention aims to solve]

[0004] To overcome at least one of the problems present in the prior art described above, the first object of the present invention is to provide a windproof and heat-insulating fabric, which comprises an inner lining layer, a middle nanofiber layer, and an outer windproof fabric layer, which are laminated in order from the inside out. The inner lining layer combines flexibility and elasticity and provides a comfortable feel against the skin, the middle nanofiber layer optimizes performance through the mixing and melting of multiple raw materials to achieve high-efficiency heat retention and antistatic properties, and the outer windproof fabric has a composite yarn knitting structure and is used to block external airflow. These three functions work together to achieve skin-friendly breathability, high-efficiency heat retention, and windproof protection for the windproof and heat-insulating fabric. The second object of the present invention is to provide a method for manufacturing the windproof and heat-insulating fabric. The third object of the present invention is to provide applications for the windproof and heat-insulating fabric. [Means for solving the problem]

[0005] Therefore, the present invention employs the following technical solutions.

[0006] A first aspect of the present invention provides a windproof and heat-insulating fabric comprising an inner lining layer, a middle nanofiber layer, and an outer windproof fabric, which are laminated in order from the inside out. The inner lining layer is manufactured by blending polyester, nylon, and spandex. The middle nanofiber layer comprises nanofibers, aerogel powder, and a functional filler, the functional filler comprising graphene, rare earth compounds, and functional additives. The outer windproof fabric is knitted with composite yarn, which comprises a core yarn and a sheath yarn covering the outside of the core yarn.

[0007] The windproof and heat-insulating fabric of this invention has a three-layer structure consisting of an inner layer, a middle layer, and an outer layer, forming the overall function of inner layer skin lining, middle layer heat retention and antistatic properties, and outer layer windproof properties. The inner lining layer is manufactured by blending raw materials polyester, nylon, and spandex, possessing excellent flexibility and elasticity, solving the problem of insufficient skin affinity of conventional fabrics. The middle nanofiber layer utilizes the low thermal conductivity of aerogel, the thermal conductivity control of graphene, the optimization of the internal structure of rare earth compounds, and the action of functional additives to achieve high-efficiency heat retention and antistatic properties. At the same time, the composite structure of the middle nanofiber and functional filler enhances the interlayer bonding effect, which is advantageous in reducing the shedding of functional filler during use and extending the lifespan of the fabric. The outer windproof fabric is advantageous in blocking external airflow, and at the same time, the composite yarn knitting structure provides good mechanical skeletal support to the fabric, preventing deformation of the fabric due to dynamic changes such as stretching or friction during use. The layered design of this windproof and heat-retaining fabric provides overall windproof, heat-retaining, antistatic, and skin-friendly properties, making it suitable for multiple applications such as outdoor sportswear, winter clothing, and functional protective clothing. This solves the problem of conventional fabrics having only one function and being limited to specific applications.

[0008] Preferably, the raw materials for the inner lining layer, calculated by mass percentage, are 52% to 72% polyester, 20% to 40% nylon, and 5% to 16% spandex. More preferably, the raw materials for the inner lining layer, calculated by mass percentage, are 56% to 70% polyester, 22% to 36% nylon, and 7% to 16% spandex.

[0009] In the inner lining layer, 52% to 72% polyester ensures basic strength and abrasion resistance as a lining, reducing pilling and damage during use; 20% to 40% nylon reinforces the fabric's moisture absorption and breathability, reducing stuffiness when worn against the skin; and 5% to 16% spandex provides good elasticity to the fabric, improving the stretching experience during activity. The raw material composition ratio of the inner lining layer provides the fabric with basic functions such as comfort, elasticity, and durability, which is advantageous for the user's long-term wear requirements.

[0010] Preferably, in the raw materials for the intermediate nanofiber layer, the nanofibers are polyurethane nanofibers, the aerogel powder is silica aerogel, the rare earth compound is at least one selected from rare earth oxides and rare earth fluorides, and the functional additive includes an antistatic agent, a dispersant, and an adhesive. More preferably, in the raw materials for the intermediate nanofiber layer, the nanofibers are polyurethane nanofibers with a number average molecular weight of 90,000 to 150,000 g / mol, the aerogel powder is silica aerogel with a particle size of 2 to 5 μm and a specific surface area of ​​700 to 1000 m². 2 The particle size is / g, the rare earth compound is at least one selected from rare earth oxides and rare earth fluorides, the average particle size of the rare earth compound is 50 to 300 nm, and the functional aid includes a quaternary ammonium salt-based antistatic agent, a polyacrylic acid ester-based dispersant, and a polyurethane-based adhesive.

[0011] Preferably, the rare earth oxide is at least one selected from cerium oxide, yttrium oxide, and neodymium oxide. More preferably, the rare earth oxide is at least one selected from cerium oxide and yttrium oxide.

[0012] Preferably, the rare earth fluoride is at least one selected from erbium fluoride, lanthanum fluoride, and neodymium fluoride. More preferably, the rare earth fluoride is at least one selected from erbium fluoride and neodymium fluoride.

[0013] Preferably, in the rare earth compound, the weight ratio of the rare earth oxide to the rare earth fluoride is (0.5~1.3):(1~2). More preferably, in the rare earth compound, the weight ratio of the rare earth oxide to the rare earth fluoride is (0.8~1.3):(1~2).

[0014] Preferably, the quaternary ammonium salt-based antistatic agent is at least one selected from cetyltrimethylammonium chloride, distearyldimethylammonium chloride, and dodecyldimethylbenzylammonium chloride. More preferably, the quaternary ammonium salt-based antistatic agent is at least one selected from distearyldimethylammonium chloride and dodecyldimethylbenzylammonium chloride.

[0015] Preferably, the polyacrylic acid ester dispersant is at least one selected from sodium polyacrylate, ammonium polyacrylate, polymethyl methacrylate-acrylic acid copolymer, and polyacrylic acid ester sodium salt-maleic anhydride copolymer. More preferably, the polyacrylic acid ester dispersant is at least one selected from ammonium polyacrylate, polymethyl methacrylate-acrylic acid copolymer, and polyacrylic acid ester sodium salt-maleic anhydride copolymer.

[0016] Preferably, in the functional additive, the weight parts ratio of the quaternary ammonium salt-based antistatic agent, the polyacrylic acid ester-based dispersant, and the polyurethane adhesive is (1.2~1.8):(0.8~1.1):(1.5~2.3). More preferably, in the functional additive, the weight parts ratio of the quaternary ammonium salt-based antistatic agent, the polyacrylic acid ester-based dispersant, and the polyurethane adhesive is (1.5~1.8):(0.8~1.1):(1.6~2.3).

[0017] In the raw materials for the intermediate nanofiber layer, polyurethane nanofibers themselves possess excellent elasticity, flexibility, and a high specific surface area, providing a relatively stable support framework for the adhesion of aerogel and functional fillers. Silica aerogel has relatively low thermal conductivity, effectively blocking heat transfer and playing a role in heat insulation. In the functional fillers, graphene is lightweight and has good conductivity, forming a conductive network in the intermediate nanofiber layer and working in cooperation with antistatic agents to provide the fabric with a lasting antistatic function. In the rare earth compounds, rare earth oxides can emit far-infrared rays, and rare earth fluorides can perform photothermal conversion. Rare earth compounds of rare earth oxides and rare earth fluorides in a weight parts ratio of (0.5~1.3):(1~2) contribute to strengthening and improving the heat retention efficiency of the intermediate nanofiber layer. Furthermore, in the functional additives, antistatic agents perform an antistatic effect, improving the wearing experience, dispersants ensure uniformity of the distribution of raw materials such as fillers, and adhesives improve overall adhesion, thereby reducing the risk of filler detachment.

[0018] Preferably, in the functional filler, the weight parts ratio of graphene, rare earth compound, and functional additive is (2-5):(0.9-2.3):(0.6-1). More preferably, in the functional filler, the weight parts ratio of graphene, rare earth compound, and functional additive is (3-5):(1-2.3):(0.6-1). Even more preferably, in the functional filler, the weight parts ratio of graphene, rare earth compound, and functional additive is (3-5):(1.5-2.3):(0.6-1).

[0019] 2-5 parts graphene contributes to the mid-layer nanofiber layer achieving good conductivity and heat conduction control capabilities, avoiding insufficient antistatic and heat retention effects due to too low a graphene content, as well as preventing the fabric from becoming stiff due to too high a graphene content. 0.9-2.3 parts rare earth compounds enhance the heat retention effect of the mid-layer and simultaneously prevent filler aggregation due to excessive use. 0.6-1 part functional additives, specifically formulated in particular ratios of antistatic agents, dispersants, and adhesives, ensure that each additive fully exerts its respective effect.

[0020] Preferably, in the intermediate nanofiber layer, the weight part ratio of the nanofibers, aerogel powder and functional filler is (6~9):(1.8~3):(0.8~1.5). More preferably, in the intermediate nanofiber layer, the weight part ratio of the nanofibers, aerogel powder and functional filler is (7~9):(2~3):(0.8~1.5). Even more preferably, in the intermediate nanofiber layer, the weight part ratio of the nanofibers, aerogel powder and functional filler is (7~9):(2~3):(1~1.5).

[0021] In the intermediate nanofiber layer, 6 to 9 parts of nanofibers are used as the base material, which can form a continuous and dense fiber network, provide a stable carrier for the aerogel and the functional filler, thereby avoiding loosening of the intermediate layer structure. 1.8 to 3 parts of aerogel powder are sufficiently filled into the gaps of the nanofibers to form a fiber-aerogel composite thermal insulation structure, ensuring the excellent thermal insulation performance of the intermediate nanofiber layer. 0.8 to 1.5 parts of the functional filler can fully exert the effects such as antistatic property, aging resistance, dispersion and adhesion without affecting the air permeability of the intermediate layer, and at the same time avoid the influence on air permeability caused by clogging of the internal structure due to excessive filler.

[0022] Preferably, in the outer layer windproof fabric, the core yarn is aramid fiber, and the sheath yarn is thermoplastic polyurethane elastic fiber.

[0023] Preferably, the basis weight of the inner lining fabric layer is 80~120g / m 2 , the thickness of the intermediate nanofiber layer is 0.1~0.3mm, and the basis weight of the outer layer windproof fabric is 100~145g / m 2 . More preferably, the basis weight of the inner lining fabric layer is 90~120g / m 2 , the thickness of the intermediate nanofiber layer is 0.15~0.3mm, and the basis weight of the outer layer windproof fabric is 110~145g / m 2 . Even more preferably, the basis weight of the inner lining fabric layer is 90~120g / m 2and the thickness of the intermediate nanofiber layer is 0.2~0.3mm, and the basis weight of the outer windproof fabric is 120~145g / m 2 .

[0024] The basis weight of the inner layer of 80~120g / m 2 achieves both the softness for skin contact and durability, avoiding the problems of being too heavy and bulky, or too lightweight and prone to damage. The thickness of 0.1~0.3mm for the intermediate layer ensures excellent thermal insulation, antistatic properties, air permeability and the like, and at the same time avoids the fabric becoming too thick and stiff. The basis weight of 100~145g / m for the outer layer 2 and the knitting of high-density composite yarn enable the outer layer to fully perform its windproof function, and avoid excessive thickness that would increase the overall weight of the fabric.

[0025] A second aspect of the present invention provides a method for manufacturing the windproof thermal insulation fabric according to the first aspect of the present invention, S1, manufacturing the inner lining fabric layer: mixing polyester, nylon and spandex, and performing spinning, knitting and pre-shrinking finishing to obtain the inner lining fabric layer; S2, manufacturing the intermediate nanofiber layer: mixing and melting nanofibers, aerogel powder and functional fillers, and performing melt-blowing spinning and drawing to form the intermediate nanofiber layer; S3, manufacturing the outer windproof fabric: knitting the core yarn and sheath yarn, and performing heat press setting to obtain the outer windproof fabric; S4, composite forming: stacking the inner lining fabric layer, the intermediate nanofiber layer and the outer windproof fabric in sequence, and performing thermal fusion bonding composite and setting treatment to obtain the windproof thermal insulation fabric.

[0026] Preferably, in step S1, the spinning employs a ring spinning process, the twist count of the spinning is 380-450 twists / m for the warp and 320-380 twists / m for the weft, and the fineness of the yarn is 14-21 tex. More preferably, in step S1, the spinning employs a ring spinning process, the twist count of the spinning is 390-450 twists / m for the warp and 330-380 twists / m for the weft, and the fineness of the yarn is 14-21 tex. Even more preferably, in step S1, the spinning employs a ring spinning process, the twist count of the spinning is 400-450 twists / m for the warp and 350-380 twists / m for the weft, and the fineness of the yarn is 16-21 tex.

[0027] Preferably, in step S2, the temperature of the mixed melt is 200-280°C, the melt-blown spinning temperature is 230-260°C, the speed is 500-800 m / s, the pressure is 0.4-0.6 MPa, and the receiving distance is 15-20 cm. More preferably, in step S2, the temperature of the mixed melt is 230-280°C, the melt-blown spinning temperature is 240-260°C, the speed is 550-800 m / s, the pressure is 0.4-0.6 MPa, and the receiving distance is 15-20 cm. Even more preferably, in step S2, the temperature of the mixed melt is 250-280°C, the melt-blown spinning temperature is 240-260°C, the speed is 650-800 m / s, the pressure is 0.5-0.6 MPa, and the receiving distance is 18-20 cm.

[0028] Preferably, in step S3, the knitted core thread feed speed is 28-33 m / min, the sheath thread feed speed is 36-42 m / min, the core thread tension is 20-25 cN, the coating rotation speed is 8000-9000 rpm, the heat press molding temperature is 150-170°C, the pressure is 1.0-1.5 MPa, and the time is 60-90 s. More preferably, in step S3, the knitted core thread feed speed is 30-33 m / min, the sheath thread feed speed is 38-42 m / min, the core thread tension is 20-25 cN, the coating rotation speed is 8000-9000 rpm, the heat press molding temperature is 155-170°C, the pressure is 1.0-1.5 MPa, and the time is 60-90 s. More preferably, in step S3, the feed speed of the knitted core thread is 30-33 m / min, the feed speed of the sheath thread is 38-42 m / min, the core thread tension is 23-25 ​​cN, the coating rotation speed is 8200-9000 rpm, the temperature of the heat press molding is 155-170°C, the pressure is 1.2-1.5 MPa, and the time is 60-90 s.

[0029] Preferably, in step S4, the temperature of the heat-seal composite is 100 to 130°C, the pressure of the heat-seal composite is 0.3 to 1 MPa, the time of the heat-seal composite is 1 to 2 min, the temperature of the molding is 80 to 100°C, and the molding time is 5 to 10 min. More preferably, in step S4, the temperature of the heat-seal composite is 105 to 130°C, the pressure of the heat-seal composite is 0.5 to 1 MPa, the time of the heat-seal composite is 1 to 2 min, the temperature of the molding is 80 to 100°C, and the molding time is 5 to 10 min. Even more preferably, in step S4, the temperature of the heat-seal composite is 110 to 130°C, the pressure of the heat-seal composite is 0.6 to 1 MPa, the time of the heat-seal composite is 1 to 2 min, the temperature of the molding is 85 to 100°C, and the molding time is 7 to 10 min.

[0030] A third aspect of the present invention provides an application of a windproof and heat-insulating fabric in the manufacture of clothing or textile products, wherein the windproof and heat-insulating fabric is the windproof and heat-insulating fabric described above, or is manufactured by the manufacturing method described above. [Effects of the Invention]

[0031] Compared to the prior art, the present invention has at least the following beneficial effects. 1) The windproof and heat-retaining fabric of this invention includes an inner lining layer, a middle nanofiber layer, and an outer windproof fabric layer, which are layered sequentially from the inside out. Furthermore, the windproof and heat-retaining fabric manufactured by rationally blending the raw material components has excellent heat retention, windproofness, breathability, antistatic properties, and durability, solving the problem of conventional fabrics having only one function and being limited to specific situations. 2) In the method for manufacturing the windproof and heat-insulating fabric of the present invention, the windproof and heat-insulating fabric is manufactured by steps such as manufacturing the inner layer lining fabric, manufacturing the middle layer nanofiber layer, manufacturing the outer layer windproof fabric, and composite molding. This manufacturing method contributes to achieving strong fusion at the interface of the three-layer structure and stabilization of the overall dimensions through precise process control, and to improving the windproof and heat-insulating effects of the windproof and heat-insulating fabric. [Modes for carrying out the invention]

[0032] The present invention will be described in more detail below through specific examples, comparative examples, and tables, but this is not limited to all discussions and data.

[0033] In the raw materials for the windproof and heat-retaining fabric, the polyurethane nanofibers were purchased from Huafeng Chongqing Spandex Co., Ltd., with model number HF-PU NF850, and a number-average molecular weight of 100,000 to 120,000 g / mol. The silica aerogel powder was purchased from Zhejiang Nanuo Technology Co., Ltd., with model number Nano-SA-P2, a particle size of 2 to 5 μm, and a specific surface area of ​​700 to 900 m². 2The particle size is / g, cerium oxide is purchased from Jining Mycrea Rare Earth Co., Ltd., particle size 50-100 μm, neodymium fluoride is purchased from Shandong Desheng New Materials Co., Ltd., particle size 150 μm, ammonium polyacrylate is purchased from ▲Yi Fang Lu Yi Chemical Co., Ltd., model number Dispersant-5020, polyurethane adhesive is purchased from Shanghai Tianyang Thermal Adhesion Materials Co., Ltd., model number JCC-PUR 5030, graphene is purchased from Changzhou Sixth Element Materials Technology Co., Ltd., model number SE1230, specific surface area 120-150 m² 2 It is / g.

[0034] The steps for manufacturing the homemade functional additive are as follows: 15 g of distearyldimethylammonium chloride, 10 g of ammonium polyacrylate, and 18 g of polyurethane adhesive are uniformly mixed to obtain the functional additive.

[0035] The steps for producing a homemade rare earth compound are as follows: 10 g of cerium oxide and 12 g of neodymium fluoride are uniformly mixed to obtain the rare earth compound.

[0036] Unless otherwise specified, the raw materials, reagents, or apparatus used in this invention can all be obtained through conventional commercial channels.

[0037] Examples of functional filler manufacturing: Manufacturing example 1: The steps for manufacturing functional fillers are as follows: The functional filler was prepared by uniformly mixing 35 g of graphene, 13 g of a proprietary rare earth compound, and 8 g of a proprietary functional additive.

[0038] Manufacturing example 2: The steps for manufacturing functional fillers are as follows: The functional filler was prepared by uniformly mixing 35 g of graphene, 20 g of a proprietary rare earth compound, and 9 g of a proprietary functional additive.

[0039] Manufacturing example 3: The steps for manufacturing functional fillers are as follows: The functional filler was prepared by uniformly mixing 45 g of graphene, 13 g of a proprietary rare earth compound, and 6 g of a proprietary functional additive.

[0040] Functional filler in manufacturing comparison example 1: The steps for manufacturing functional fillers are as follows: The functional filler was prepared by uniformly mixing 20 g of graphene, 25 g of a proprietary rare earth compound, and 1 g of a proprietary functional additive.

[0041] Examples of windproof and heat-retaining fabrics: This is a windproof and heat-retaining fabric, manufactured by the following steps. S1. Manufacturing of the inner lining layer: First, 520-720g of polyester, 200-400g of nylon, and 50-160g of spandex were mixed and spun using a ring spinning process, controlling the number of twists in the warp to 380-450 twists / m, the number of twists in the weft to 320-380 twists / m, and the fineness of the yarn to 14-21 tex. After spinning was completed, the fabric was knitted with the warp density controlled to 380-450 threads / 10cm, the weft density to 320-380 threads / 10cm, the warp tension to 20-30 cN, the weft tension to 15-25 cN, and the knitting speed to 80-120 rpm. The fabric was woven on a raw loom and subjected to a pre-shrinkage treatment at a temperature of 85-95°C to obtain the inner lining layer. S2. Production of the intermediate nanofiber layer: 600-900g of nanofibers, 180-300g of aerogel powder, and 80-150g of functional filler were mixed and melted at a temperature of 200-280°C to obtain a composite melt. The composite melt was then stretched and refined in a melt-blown process with a spinning temperature of 230-260°C, a speed of 500-800m / s, and a pressure of 0.4-0.6MPa, under conditions of an airflow velocity of 500-800m / s, an airflow pressure of 0.4-0.6MPa, and an airflow temperature of 230-260°C, followed by cooling and solidification. The mixture was collected at a receiving distance of 15-20cm to obtain the intermediate nanofiber layer. S3. Manufacturing of the outer layer windproof fabric: The core yarn feed speed was set to 28-33 m / min, the sheath yarn feed speed to 36-42 m / min, the core yarn tension to 20-25 cN, and the covering rotation speed to 8000-9000 rpm to manufacture the composite yarn. The fabric was then heat-pressed for 60-90 seconds under conditions of a temperature of 150-170°C and a pressure of 1.0-1.5 MPa to obtain the outer layer windproof fabric. S4. Composite molding: The inner lining layer, the middle nanofiber layer, and the outer windproof fabric were layered in order, and heat fusion bonding was performed at a temperature of 100-130°C and a pressure of 0.3-1 MPa. A final shaping treatment was then performed at a temperature of 80-100°C for 5-10 minutes to obtain the windproof and heat-insulating fabric.

[0042] Example 1: This is a windproof and heat-retaining fabric, manufactured by the following steps. S1. Manufacturing of the inner lining layer: First, 600g of polyester, 300g of nylon, and 100g of spandex were mixed and spun using a ring spinning process, controlling the warp twist count to 420 twists / m, the weft twist count to 350 twists / m, and the yarn fineness to 16tex. After spinning was completed, the fabric was knitted with the warp density controlled to 420 threads / 10cm, the weft density to 350 threads / 10cm, the warp tension to 25cN, the weft tension to 18cN, and the knitting speed to 100rpm. The fabric was woven on a raw loom and subjected to a pre-shrinkage treatment at a temperature of 90°C to obtain the inner lining layer. S2. Production of the intermediate nanofiber layer: 600 g of polyurethane nanofibers, 200 g of silica aerogel powder, and 100 g of the functional filler from Production Example 1 were mixed and melted at a temperature of 250°C to obtain a composite melt. The composite melt was then stretched and refined in a melt-blown process with a spinning temperature of 230°C, a speed of 600 m / s, and a pressure of 0.5 MPa, under conditions of an airflow velocity of 600 m / s, an airflow pressure of 0.5 MPa, and an airflow temperature of 230°C, and then cooled and solidified. The mixture was collected at a receiving distance of 18 cm to obtain the intermediate nanofiber layer. S3. Manufacturing of the outer layer windproof fabric: The core yarn feed speed was set to 30 m / min, the sheath yarn feed speed to 40 m / min, the core yarn tension to 23 cN, and the covering rotation speed to 8500 rpm to manufacture the composite yarn. The fabric was then heat-pressed for 80 seconds under conditions of a temperature of 160°C and a pressure of 1.2 MPa to obtain the outer layer windproof fabric. S4. Composite molding: The inner backing fabric layer, the middle nanofiber layer, and the outer windproof fabric were layered in order, and heat-sealed composite was performed at a temperature of 110°C and a pressure of 0.8 MPa. A final shaping treatment was then performed at a temperature of 90°C for 10 minutes to obtain the windproof and heat-insulating fabric.

[0043] Example 2: The method for manufacturing the windproof and heat-retaining fabric and the amounts of each raw material used are the same as in Example 1. The only difference is that in Example 2, the amounts of polyester, nylon, and spandex used in step S1 are 520g, 400g, and 80g, respectively.

[0044] Example 3: The method for manufacturing the windproof and heat-retaining fabric and the amounts of each raw material used are the same as in Example 1. The only difference is that in Example 3, the amounts of polyester, nylon, and spandex used in step S1 are 720g, 210g, and 70g, respectively.

[0045] Example 4: The manufacturing method for the windproof and heat-retaining fabric and the amounts of each raw material used are the same as in Example 1. The only difference is that in Step S2 of Example 4, the functional filler used in Manufacturing Example 1 is replaced with the same amount of the functional filler used in Manufacturing Example 2.

[0046] Example 5: The method for manufacturing the windproof and heat-retaining fabric and the amounts of each raw material used are the same as in Example 1. The only difference is that in Example 5, the functional filler used in step S2 of Manufacturing Example 1 is replaced with the functional filler used in Manufacturing Example 3.

[0047] Example 6: The method for manufacturing the windproof and heat-retaining fabric and the amounts of each raw material used are the same as in Example 1. The only difference is that in Example 6, the amounts of polyurethane nanofibers, silica aerogel powder, and the functional filler used in step S2 are 700g, 250g, and 120g, respectively.

[0048] Example 7: The method for manufacturing the windproof and heat-retaining fabric and the amounts of each raw material used are the same as in Example 1. The only difference is that in Example 7, the amounts of polyurethane nanofibers, silica aerogel powder, and the functional filler used in step S2 are 850g, 300g, and 80g, respectively.

[0049] Comparative Example 1: The method for manufacturing the windproof and heat-retaining fabric and the amounts of each raw material used are the same as in Example 1. The only difference is that in Comparative Example 1, the amounts of polyester, nylon, and spandex used in step S1 are 520g, 400g, and 180g, respectively.

[0050] Comparative Example 2: The manufacturing method for the windproof and heat-retaining fabric and the amounts of each raw material used are the same as in Example 1. The only difference is that in Comparative Example 2, the functional filler used in step S2 of Manufacturing Example 1 is replaced with the same amount of the functional filler used in Manufacturing Comparative Example 1.

[0051] Comparative Example 3: The method for manufacturing the windproof and heat-retaining fabric and the amounts of each raw material used are the same as in Example 1. The only difference is that in Comparative Example 3, the amounts of polyurethane nanofibers, silica aerogel powder, and the functional filler used in step S2 are 850g, 400g, and 70g, respectively.

[0052] Material performance testing: The windproof and heat-retaining fabrics obtained in Examples 1-7 and Comparative Examples 1-3 were subjected to performance tests, and the test methods are as follows. 1. Thermal resistance value: The test was conducted in accordance with GB / T 11048-2018. 2. Air permeability: Tests were conducted in accordance with GB / T 5453-1997. 3. Water vapor permeability: The test was conducted in accordance with GB / T 12704.1-2009. 4. Static voltage half-life: Tests were conducted in accordance with GB / T 12703.1-2021. 5. Breaking strength: Tests were conducted in accordance with GB / T 3923.1-2013.

[0053] The test performance of the windproof and heat-retaining fabrics for Examples 1-7 and Comparative Examples 1-3 is shown in Table 1 below.

[0054] Table 1 Performance test results for Examples 1-7 and Comparative Examples 1-3 [Table 1]

[0055] The windproof and heat-insulating fabrics of Examples 1-7 are constructed by laminating an inner lining layer, a middle nanofiber layer, and an outer windproof fabric in order from the inside out. The process conditions of each step are optimized, and in particular, the windproof and heat-insulating fabric produced by a composite system consisting of a middle nanofiber layer, a functional filler with specific components and proportions, nanofibers, and aerogel has excellent heat retention properties, a thermal resistance value of 0.45-0.54 clo, good breathability and moisture permeability, with an air permeability of 10.5-14.2 mm / s and a moisture permeability of 6635-6960 g / m². 2 With a 24-hour lifespan, good antistatic properties, a static voltage half-life in the range of 1.5 to 2.1 seconds, a longitudinal breaking strength of 567 to 620 N / 5 cm, and a weft breaking strength of 461 to 502 N / 5 cm, this three-layer structure design ensures that the fabric achieves a good balance between heat retention, windproofness, breathability, antistatic properties, and durability, making it widely applicable to outdoor sportswear, winter clothing, and functional protective clothing, and particularly suitable for use in cold, windy environments.

[0056] Comparative Example 1 differs from Example 1 in that its manufacturing method and the amount of each raw material used are the same as in Example 1. The difference is that the mass percentage of raw materials in the inner lining layer of Comparative Example 1 is 52% polyester, 40% nylon, and 18% spandex, and the mass percentage of spandex is outside the scope of the technical solution of the present invention. As can be seen from the results, the thermal resistance value of the windproof and heat-insulating fabric of Comparative Example 1 shows a significant decrease in both the warp breaking strength and the weft breaking strength, and the static voltage half-life is extended to 3.6 s. This is thought to be because the spandex occupancy rate in Comparative Example 1 is too high, destroying the bonding strength of the polyester and nylon blend, resulting in insufficient mechanical skeletal support of the inner lining layer, loosening of the fabric structure, and thereby reducing its windproof and heat-insulating effect and mechanical strength. At the same time, the loosening of the structure makes it more susceptible to deformation, causing localized fractures in the internal electrostatic conduction paths, and further affecting the overall antistatic performance.

[0057] Comparative Example 2 uses the same manufacturing method and quantities of each raw material as Example 1, except that the middle layer nanofiber layer in Comparative Example 2 uses the same functional filler as in Comparative Example 1. As can be seen from the test results, the thermal resistance of the windproof and heat-insulating fabric of Comparative Example 2 decreased to 0.41 clo, and the air permeability and moisture permeability were 15.6 mm / s and 7020 g / m², respectively. 2 The static voltage half-life was significantly extended to 4.8 s, and the breaking strength in the warp and weft directions decreased to 519 N / 5 cm and 425 N / 5 cm, respectively. This is because the amount of graphene used in the functional filler of Manufacturing Comparative Example 1 was insufficient, preventing the formation of a continuous conductive network in the middle nanofiber layer, thus preventing rapid dissipation of static electricity and significantly reducing its antistatic performance. On the other hand, the amount of rare earth compounds used was excessive, causing the filler to aggregate easily and resulting in uneven dispersion, which disrupted its composite thermal insulation structure, affecting the thermal insulation effect and interlayer bonding strength, and reducing both heat retention and mechanical performance.

[0058] Comparative Example 3 differs from Example 1 in that its manufacturing method and the amount of each raw material used are the same as in Example 1. The only difference is that the raw material blending ratio of the middle layer nanofiber in Comparative Example 3 is adjusted to 850g of polyurethane nanofiber, 400g of silica aerogel powder, and 70g of functional filler. As can be seen from the test results, the thermal resistance value of the windproof and heat-insulating fabric of Comparative Example 3 is 0.43 clo, the air permeability is 13.5 mm / s, and the moisture permeability is 6890 g / m². 2 The half-life of the static voltage was extended to 3.2 s, and the breaking strength in the warp and weft directions was 574 N / 5 cm and 461 N / 5 cm, respectively. This is thought to be because in Comparative Example 3, the amount of aerogel powder used was too high and the amount of functional filler used was too low, causing the excess aerogel powder to accumulate in the nanofiber network, partially blocking the voids in the middle nanofiber layer, which may further affect the moisture permeability efficiency. At the same time, because there was insufficient functional filler, the content of its antistatic component, such as graphene or antistatic agent, was relatively low, making it impossible to form effective conductive passages, thereby reducing its antistatic performance.

[0059] Clearly, the above embodiments of the present invention are illustrative to illustrate the present invention clearly and do not limit the embodiments of the present invention. Those skilled in the art can make other different forms of changes or variations based on the above description, and any obvious changes or variations described in the technical solutions of the present invention are included within the scope of protection of the present invention.

Claims

1. A windproof and heat-retaining fabric comprising an inner layer lining, a middle layer nanofiber layer, and an outer layer windproof fabric, which are layered in order from the inside to the outside. The aforementioned inner lining layer is manufactured by blending polyester, nylon, and spandex. The raw materials for the intermediate nanofiber layer include nanofibers, aerogel powder, and a functional filler, and the functional filler includes graphene, a rare earth compound, and a functional additive. The outer windproof fabric is made of composite yarn, and the composite yarn includes a core yarn and a sheath yarn covering the outside of the core yarn. In the raw materials for the intermediate nanofiber layer, the nanofibers are polyurethane nanofibers, the aerogel powder is silica aerogel, the rare earth compound is at least one selected from rare earth oxides and rare earth fluorides, and the functional additive includes an antistatic agent, a dispersant and an adhesive. In the functional filler, the weight parts ratio of graphene, rare earth compound, and functional additive is (2-5):(0.9-2.3):(0.6-1), A windproof and heat-retaining fabric characterized in that, in the middle layer of nanofibers, the weight parts ratio of the nanofibers, aerogel powder, and functional filler is (6-9):(1.8-3):(0.8-1.5).

2. The windproof and heat-retaining fabric according to claim 1, characterized in that the inner lining layer, when calculated by mass percentage, consists of 52% to 72% polyester, 20% to 40% nylon, and 5% to 16% spandex.

3. The aforementioned rare earth oxide is at least one selected from cerium oxide, yttrium oxide, and neodymium oxide. The windproof and heat-insulating fabric according to claim 1, characterized in that the rare earth fluoride is at least one selected from erbium fluoride, lanthanum fluoride, and neodymium fluoride.

4. The basis weight of the aforementioned inner lining fabric layer is 80 to 120 g / m². 2 The thickness of the middle layer nanofiber is 0.1 to 0.3 mm, and the basis weight of the outer windproof fabric is 100 to 145 g / m². 2 The windproof and heat-retaining fabric according to feature 1.

5. S1. Manufacturing of the inner lining fabric: A step of obtaining the inner lining fabric by mixing polyester, nylon and spandex, spinning, knitting, and pre-shrinking and finishing, S2. Manufacturing of the intermediate nanofiber layer: A step of forming an intermediate nanofiber layer by mixing and melting nanofibers, aerogel powder and functional filler, followed by melt spinning and stretching, S3. Manufacturing of the outer layer windproof fabric: The steps include knitting and heat-pressing the core yarn and sheath yarn to obtain the outer layer windproof fabric, A method for manufacturing a windproof and heat-insulating fabric according to any one of claims 1 to 4, characterized by comprising the step of S4, composite molding: layering an inner backing fabric layer, a middle nanofiber layer, and an outer windproof fabric in order, followed by heat fusion bonding and shaping to obtain the windproof and heat-insulating fabric.

6. The method for manufacturing a windproof and heat-insulating fabric according to claim 5, characterized in that in step S4, the temperature of the heat-seal composite is 100 to 130°C, the pressure of the heat-seal composite is 0.3 to 1 MPa, the time of the heat-seal composite is 1 to 2 min, the temperature of the final molding is 80 to 100°C, and the time of the final molding is 5 to 10 min.

Citation Information

Patent Citations

  • Aerogel composite fabric utilizing aqueous adhesive and preparation method thereof

    CN104015414A

  • Aerogel composite cloth taking hot melt adhesive as binder and preparation method for composite cloth

    CN104029429A

  • Composite fabric and preparation method thereof

    CN106626634A

  • Graphene composite fiber

    CN107254722A

  • Waterproof screen cloth and preparation method thereof

    CN111139583A